A Machine-to-Machine protocol benchmark for eHealth applications – Use case: Respiratory rehabilitation. Issue 129 (June 2016) - Talaminos-Barroso, Alejandro; Estudillo-Valderrama, Miguel A.; Roa, Laura M.; Reina-Tosina, Javier; Ortega-Ruiz, Francisco
Highlights: The software tool presented allows the deployment of different benchmarking tests for M2M protocols. The most relevant M2M protocols were evaluated considering different specific performance metrics. Benchmark results allowed to select the most suitable M2M protocol a clinical case of use: respiratory rehabilitation. Abstract: Background: M2M (Machine-to-Machine) communications represent one of the main pillars of the new paradigm of the Internet of Things (IoT), and is making possible new opportunities for the eHealth business. Nevertheless, the large number of M2M protocols currently available hinders the election of a suitable solution that satisfies the requirements that can demand eHealth applications. Objectives: In the first place, to develop a tool that provides a benchmarking analysis in order to objectively select among the most relevant M2M protocols for eHealth solutions. In the second place, to validate the tool with a particular use case: the respiratory rehabilitation. Methods: A software tool, called Distributed Computing Framework (DFC), has been designed and developed to execute the benchmarking tests and facilitate the deployment in environments with a large number of machines, with independence of the protocol and performance metrics selected. Results: DDS, MQTT, CoAP, JMS, AMQP and XMPP protocols were evaluated considering different specific performance metrics, including CPU usage, memory usage, bandwidth consumption, latency and jitter. The results obtained allowed to validate a case of use: respiratory rehabilitation of chronic obstructive pulmonary disease (COPD) patients in two scenarios with different types of requirement: Home-Based and Ambulatory. Conclusions: The results of the benchmark comparison can guide eHealth developers in the choice of M2M technologies. In this regard, the framework presented is a simple and powerful tool for the deployment of benchmark tests under specific environments and conditions.